Carpal Tunnel Syndrome-A Battery of Tests can Improve the Diagnosis - Pandey, Alok; Kumar, Bhaskarananda (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: The gold standard for diagnosis of carpal tunnel syndrome (CTS) is not well defined. At times, patients of suspected carpal tunnel syndrome fail to respond to treatment if the diagnosis is based on symptoms alone or on one or two clinical tests probably because the diagnosis is not correct. The purpose of this study was to compare the relative merits of various diagnostic modalities in establishing the diagnosis of CTS and also to define the accurate test or combination of tests to help diagnose and manage CTS. MATERIAL AND METHODS: Patients presenting with symptoms suggestive of CTS were evaluated using (i) Clinical Provocative tests - Durkan's test and Phalen's test, (ii) Tests for sensory perception thresholds using Semmes-Weinstein monofilament nylons (iii) Nerve conduction studies predominately sensory and motor and (iv) Gray scale sonography. RESULTS: When a positive Phalen's test was taken as reference, the positive predictive value of Durkan's test and ultrasonography was 100%, Nylon perception test and neurophysiological studies had a value of 90 and 89% respectively. When Durken's test was used as reference, ultrasonography had a positive predictive value 0f 98% followed by nylon perception testing - 94%. Phalen's test and neurophysiological studies had values of the order of 92 and 88% respectively. CONCLUSION: Our observations suggest that clinical history and physical examination can be used to screen the patients. The perception threshold testing with monofilament nylons and ultrasonographic examination of carpal tunnel (CT) improve the diagnosis. In addition, ultrasonographic examination of CT provides the information on anatomy and condition of the contents of CT and help planning the treatment. A combination of clinical provocative tests, Semmes-Weisntein monofilament testin and high frequency sonography could be considered as definitive diagnostic battery for diagnosing carpal tunnel syndrome. Journal of Universal College of Medical Sciences Vol. 3, No. 1, 2015: 26-30